2019
DOI: 10.1038/s41388-019-0853-z
|View full text |Cite
|
Sign up to set email alerts
|

TBX2 interacts with heterochromatin protein 1 to recruit a novel repression complex to EGR1-targeted promoters to drive the proliferation of breast cancer cells

Abstract: Early Growth Response 1 (EGR1) is a stress response transcription factor with multiple tumour suppressor roles in breast tissue, whose expression is often lost in breast cancers. We have previously shown that the breast cancer oncogene TBX2 (T-BOX2) interacts with EGR1 to co-repress EGR1-target genes including the breast tumour suppressor NDRG1. Here, we show the mechanistic basis of this TBX2 repression complex. We show that siRNA knockdown of TBX2, EGR1, Heterochromatin Protein 1 (HP1) isoforms and the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 34 publications
(50 reference statements)
4
31
0
Order By: Relevance
“…The high expression of EGR1 exhibited a correlation with ne RFS. Crawford et al found the expression of EGR1 was reduced in BRCA, which was in agreement with our results [28]. Besides, active EGR1 elevated PAC1 expression with excessive oxygen species, ultimately causing the chromatin remodeling mechanism of effector T cells [29].…”
Section: Discussionsupporting
confidence: 92%
“…The high expression of EGR1 exhibited a correlation with ne RFS. Crawford et al found the expression of EGR1 was reduced in BRCA, which was in agreement with our results [28]. Besides, active EGR1 elevated PAC1 expression with excessive oxygen species, ultimately causing the chromatin remodeling mechanism of effector T cells [29].…”
Section: Discussionsupporting
confidence: 92%
“…As previously reported, EGR1 plays multiple tumor suppressor roles in breast cancer, in which its expression is often lost ( Crawford et al, 2019 ); EGR2 is a growth inhibitor when upregulated in tumor cells ( Salotti et al, 2015 ), exogenous expression of EGR2 can also suppress the growth of tumor cells ( Unoki and Nakamura, 2003 ), but its role in breast cancer is rarely reported; downregulation of EGR3 can promote the migration and invasion of hepatocellular carcinoma (HCC) ( Wangdong et al, 2017 ), high expression level of EGR3 was discovered in prostate cancer samples ( Pio et al, 2013 ), but its role in breast cancer is also rarely reported. Few researches reported EGR4 in malignant tumors; only some articles reported that EGR4 might promote NSCLC ( He et al, 2019 ), small cell lung cancer (SCLC) ( Matsuo et al, 2014 ), and cholangiocarcinoma (CHOL) to develop ( Gong et al, 2020 ).…”
Section: Discussionmentioning
confidence: 74%
“…Recently, accumulating studies show that certain T-box genes also play an important role in cancer progression. Upregulated TBX2 and TBX3 promoted tumorigenesis and progression of different types of cancer (Durbin et al, 2018;Crawford et al, 2019;Krstic et al, 2019). In contrast, a recent study revealed that TBX1 functions as a tumor suppressor in PTC (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies had demonstrated that mutations in different members of the T-box family result in developmental syndromes, characterized by organ deformity and body structure defects (Miller et al, 2010). In recent years, increasing studies reported that the T-box genes might also function in tumorigenesis and progression in certain cancers (Crawford et al, 2019;Krstic et al, 2019). As a member of the T-box gene family, T-box transcription factor 22 (TBX22) mutations caused a high risk of incidence in several diseases, including non-syndromic cleft palate, hypodontia, and ankyloglossia (Braybrook et al, 2001;Kantaputra et al, 2011).…”
Section: Introductionmentioning
confidence: 99%